Applying Jakob Nielsen's rules on Kor Suksis UMP portal (KSUP) - Noor Shafika Syuhada, Rosli (2012)
The objective of this thesis is to present a well-design website that offers services to Kor Sukarelawan Polis Siswa-Siswi of Universiti Malaysia Pahang or also known as Kor SUKSIS,UMP.Kor SUKSIS is the Police Undergraduate Voluntary Corp which is an undergraduate police volunteer organization in Malaysia.The website will be developed with criteria of a portal which provides a platform for communication between members and the instructors of the organization.Another objective is to make a research in Human Computer Interaction(HCI)area which is in the context of web portal. The issues and challenges arise during the research can help developer to design a usable and effective web portal. Besides,HCI also concerned with the understanding, designing and evaluating computer system for human use.In this research,an issue which related to the development of KSUP has been examined which is how to ensure the design of a web portal offer good HCI.In addition,computers are used by different kinds of people.So, it is important to design HCI that supports needs, knowledge and skills of the intended users.Therefore,in order to design a portal that is accessible by all users,developer should taking account on the client background.To achieve this objective,a research on client background which is the instructors and member of Kor SUKSIS UMP has been done.Besides,in order to ensure the website have a well-design and easier to use,heuristic evaluation will be performed using Jakob Nielsenâs rules, which is the guidelines for making sites user friendly. However,using only Jakob Nielsenâs rules during development process is not enough.Therefore,a usability testing will be implemented on the websites before deliver it to the end user.This step is important in order to ensure the website have met user requirement.